1984
DOI: 10.2214/ajr.143.3.543
|View full text |Cite
|
Sign up to set email alerts
|

Scintigraphy of gastrointestinal hemorrhage: superiority of 99mTc red blood cells over 99mTc sulfur colloid

Abstract: The relative efficacy of 99mTc sulfur colloid and in vitro-labeled 99mTc red blood cells in detecting and localizing gastrointestinal hemorrhage was evaluated in a prospective tandem study of 100 patients referred for suspicion of gastrointestinal tract hemorrhage. Thirty-eight true-positive scintigrams were obtained with 99mTc red blood cells, whereas 99mTc sulfur colloid detected only five sites of hemorrhage. Scintigraphic findings were corroborated by clinical, endoscopic, arteriographic, and surgical find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
4

Year Published

1987
1987
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(30 citation statements)
references
References 0 publications
0
26
0
4
Order By: Relevance
“…99m TcRBCs are the radiopharmaceutical of choice for performing GIBS because of an intravascular half-life that allows continuous imaging of the gastrointestinal tract over many hours (40)(41)(42). The superior clinical utility of 99m Tc-RBCs over early studies using 99m Tc-sulfur colloid has been demonstrated in comparison studies (40)(41)(42).…”
Section: Radiopharmaceuticalsmentioning
confidence: 99%
“…99m TcRBCs are the radiopharmaceutical of choice for performing GIBS because of an intravascular half-life that allows continuous imaging of the gastrointestinal tract over many hours (40)(41)(42). The superior clinical utility of 99m Tc-RBCs over early studies using 99m Tc-sulfur colloid has been demonstrated in comparison studies (40)(41)(42).…”
Section: Radiopharmaceuticalsmentioning
confidence: 99%
“…Although both 99m Tc-sulfur colloid and 99m Tc-labeled RBCs have been used for gastrointestinal bleeding scintigraphy, clinical studies comparing the 2 radiopharmaceuticals in the same patients demonstrate the clear superiority of the 99m Tc-RBC procedure (43,44). The Society of Nuclear Medicine procedure guidelines for gastrointestinal bleeding scintigraphy recommend the use of in vitro labeled 99m TcRBCs to minimize elution of the label from the RBCs (36).…”
Section: Gastrointestinal Bleeding Scintigraphymentioning
confidence: 99%
“…The advantage of 99mTc sulfur colloid is that it is a readily available, quickly prepared radiopharmaceutical that can accurately lo cate active GI bleeding; its disadvantage is that it is insensitive for the detection of GI bleeding. In a study of 100 patients referred for suspicion of GI bleeding and studied sequentially with both radiolabels, hem orrhage was found in 30 patients using 99raTc red cells and in only 5 of the same 30 patients with 99mTc sul fur colloid [48]. Thus, we prefer to use 99mTc red blood cells, which although less convenient to pre pare, are more sensitive for the detection and local ization of bleeding, especially in this population that often is bleeding intermittently.…”
Section: Techniquementioning
confidence: 99%